The social construction of 101 non-emergency video relay services for deaf signers - Skinner, Robert A. (International journal of police science & management, 2021)
How the police prepare for and engage with a citizen who is deaf and uses British Sign Language (BSL) is a national problem. From the perspective of deaf sign language users, the police remain largely inaccessible and unprepared in how to accommodate their linguistic needs. Four regional forces have responded to this issue by introducing a local solution, a bespoke 101 non-emergency video relay service (101VRS). Independent VRS companies function as the auxiliary service, mediating video calls to a 101 helpline. This service was identified as a simple solution that relied on minimal resourcing and input from the police. In using Pinch and Bijker’s social construction of technology (SCOT) framework, we look at competing interpretations of the 101VRS concept and how this has led to a range of intended and unintended solutions and problems (Pinch TJ and Bijker WE (1984) The social construction of facts and artefacts: or how the sociology of science and the sociology of technology might benefit each other. Social Studies of Science 14(3): 399–441). To maintain the investment in improving access to the police, we recommend harmonization of 101VRS nationally, and ongoing consultation with how front-line services can become better prepared at assisting deaf citizens.